Prevalence of Atypical Infections in Male Patients with Chronic Pelvic Pain - Nagoda, Elizabeth; Demus, Timothy; Jivanji, Dhaval; Cragnotti, Giovanni; Bui, Anthony; Polackwich, Alan (Archives of Men’s Health, 2022)
Introduction: Atypical infections are often considered as a potential etiology for men with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). We aimed to describe the prevalence of atypical infections in this patient population to inform clinical management for male patients complaining of pelvic pain. Methods: We retrospectively reviewed patients at a single center from January 2016 to January 2019. We included patients with CP/CPPS Type III diagnosed with pelvic or genital pain in the absence of bacterial infection. All patients underwent an atypical infection panel. The primary outcome measure was the presence of any atypical infection. Results: In total, 345 patients met the inclusion criteria. Of those, 9/345 (2.6%) had an atypical infection (5 mycoplasma and 4 ureaplasma). The mean age of patients with positive atypical infections was 34 compared to the overall study population (44 years, P=0.01). Two patients with atypical infections were also followed for infertility. Urinalysis was available for 6 of the 9 patients with positive atypical infection: 50% (3 out of 6) were normal and 50% (3 out of 6) had >5 WBC/hpf. Symptoms resolved in 66% (2 out of 3) of the patients with positive atypical infection with available follow-up data. Conclusion: Atypical infectious agents were uncommon causes of CP/CPPS. Screening for atypical microbes such as chlamydia, ureaplasma, or mycoplasma may not be necessary for male patients complaining of pelvic or genital pain.